Cytoarchitecture of Zika Virus Infection in Human Neuroblastoma and Aedes albopictus Cell Lines - Offerdahl, Danielle K (Virology, 2016)
The Zika virus (ZIKV) pandemic is a global concern due to its role in the development of congenital anomalies of the central nervous system. This mosquito-borne flavivirus alternates between mammalian and mosquito hosts, but information about the biogenesis of ZIKV is limited. Using a human neuroblastoma cell line (SK-N-SH) and an Aedes albopictus mosquito cell line (C6/36), we characterized ZIKV infection by immunofluorescence, transmission electron microscopy (TEM), and electron tomography (ET) to better understand infection in these disparate host cells. ZIKV replicated well in both cell lines, but infected SK-N-SH cells suffered a lytic crisis. Flaviviruses scavenge host cell membranes to serve as replication platforms and ZIKV showed the hallmarks of this process. Via TEM, we identified virus particles and 60–100nm spherular vesicles. ET revealed these vesicular replication compartments contain smaller 20–30nm spherular structures. Our studies indicate that SK-N-SH and C6/36 cells are relevant models for viral cytoarchitecture study.